AB1126 Whole-body magnetic resonance imaging in the assessment of disease activity in juvenile dermatomyositis. (23rd January 2014) - Malattia, C.; Madeo, A.; Pistorio, A.; Providenti, A.; Damasio, M.B.; Mattiuz, C.; Pederzoli, S.; Mazzoni, M.; Beltramo, A.; Buoncompagni, A.; Martini, A.
Abstract : Background: Magnetic resonance imaging (MRI) has been suggested as a valuable technique for diagnosis of myositis because of its high sensitivity to the presence of inflammation. So far all MRI studies in juvenile dermatomyositis (JDM) have focused on the thighs muscles. Whole-body MRI (WB-MRI) is a new technique which allows to screen the entire muscular-skeletal system and it gives a complete assessment of the total inflammatory burden in patients with idiopathic inflammatory myopathies (IIM). Despite that, its potentialities in children with JDM have never been explored. Objectives: to evaluate the contribution ofWB-MRI examination to the clinical assessment of JDM and to investigate its feasibility and validity in the assessment of disease activity. Methods: WB-MR images were obtained from 30 JDM patients (12M;18F, median age 8.6 years) and from 30 patients (13M; 17F, median age 10.4 years) with no inflammatory myopathies (control group), using a 1.5 Tesla and Short Tau Inversion Recovery (STIR) sequences. Signal intensity was scored using a 0-2 point scale in 42 muscular groups; myofascial and subcutaneous tissue inflammation were assessed using a 0-1 point scale. Validation procedures included the analysis of reliability, construct validity, discriminant validity and sensitivity to change. Results: WB-MRI revealed asymptomatic distal legs muscle inflammation in 21 out of 30 patients (70%) and asymptomatic forearm muscle inflammation in 15 out of 30 patients (50%). Twenty-seven patients showed a typical patchy and heterogeneous muscular inflammation. In 3 patients the abnormal hyperintense areas tended to be diffusely and homogeneously distributed in the muscle. Fascial and subcutaneous tissue inflammation were detected in 9 out of 30 (30%) and 18 out of 30 (60%) patients, respectively. Only 1 out of 30 controls showed signal changes in muscle and subcutaneous tissue, revealing an excellent discriminant validity of the WB-MRI score. The inter- and intra-reader agreement for the muscular, subcutaneous and fascial WB-MRI scores were excellent (intra-class correlation coefficient >0.8). WB-MRI total score correlated with clinical measures of disease activity (Manual Muscle Test (MMT) rs=0.86, Childhood Myositis Assessment Scale (CMAS) rs=0.85, and physician's assessment of disease activity: rs=0.75) and it showed a higher responsiveness to change (standardized response mean=0.86) compared to MMT (SRM=0.51), CMAS (SRM=0.28) and physician's assessment of disease activity (SRM =0.63). Conclusions: WB-MRI provides additional information to the clinical assessment by revealing a widerinvolvement of muscle groups. WB-MRI score allows to reliably visualize the extent of theinflammatory process inmultiple sites (skeletal muscle, subcutaneous tissue, fascia), and therefore it represents a promising non invasive tool to estimate total disease burden, to adjust treatment to disease severity and to monitor treatment efficacy in JDM. References: Cantwell C et al. A comparison of inflammatory myopathies at whole-body turbo STIR MRI. Clinical Radiology 2005; 60: 261-267. Disclosure of Interest: None Declared